Randomized clinical trials of physical therapy for cerebral palsy: A review of study outcomes, methodological quality, and publication merits - Menegol N.A.* (2023)
© 2023 Lippincott Williams and Wilkins. All rights reserved.The study aimed to examine the main characteristics of clinical trials of motor interventions in physical therapy in children with cerebral palsy (CP). The Physiotherapy Evidence Database (PEDro) was used to collect information on clinical trials regarding motor outcomes in physical therapy in children with CP. Two reviewers independently screened, selected the studies, and extracted data. The characteristics extracted were CP subtype; age group; gross motor function and manual motor ability; methodological quality; open access status; 2020 journal impact factor, Consolidated Standards of Reporting Trials (CONSORT) endorsement; primary outcome; intervention adopted, and assessment instruments. The search strategy resulted in 313 articles from 120 different journals. Most of the clinical trials included participants with spastic bilateral subtype, aged between 6 and 12-14;years old, and with fewer limitations in gross and manual motor abilities. The most used primary outcomes covering the International Classification of Functioning, Disability and Health (ICF) domain of activity were gross motor function (18.8%) and upper limb and hand function (16.3%), with the Gross Motor Function Measurement being the most frequently used instrument (19.8%). Articles with better scores on the PEDro scale were published in journals with a higher impact factor, and higher rates of CONSORT endorsement, and most were not open access. Clinical trials investigating motor interventions used in physical therapy for children with CP tend to focus on patients with milder gross and manual motor function impairments and often explore the body function domain of the ICF. Furthermore, these studies have moderate methodological quality, and a substantial proportion of them fail to follow adequate reporting and methodological recommendations.